Effectiveness and Safety of Avatrombopag in Liver Cancer Patients with Severe Thrombocytopenia: Real-World Data and Challenges. (9th November 2022) - Huang, Ao; Chen, Jia-Feng; Wu, Jian-Zhang; Gao, Zheng; Shi, Ying-Hong; Fu, Xiu-Tao; Zhang, Xin; Liu, Wei-Ren; Gao, Qiang; Sun, Hui-Chuan; Shi, Guo-Ming; Fan, Jia; et al.
Abstract : Background . Avatrombopag has been approved in patients who have severe thrombocytopenia (<50 × 10 9 /L) and chronic liver disease (CLD) while receiving invasive procedures. The real-world application and effectiveness of avatrombopag in the subgroup patients with liver cancer remain unknown. Methods . Liver cancer patients (including primary liver cancer and colorectal cancer liver metastasis) who had severe thrombocytopenia and received avatrombopag were retrospectively enrolled. Avatrombopag dose, peak and absolute platelet count increase, combination treatment with other thrombopoietic agents, responder (peak count ≥50 × 10 9 /L with absolute increase ≥20 × 10 9 /L) rate, and anticancer treatment effect were analyzed. Thrombosis and bleeding events were assessed. Results . In total, 93 patients were enrolled, with 72 and 21 in the CLD and non-CLD groups, respectively. Patients with CLD had hepatitis B or C, larger spleen volume, and a higher cirrhosis degree. Baseline platelet counts were similar between two groups (median, 37.0 × 10 9 /L vs. 39.0 × 10 9 /L; P = 0.594 ), while patients without CLD had higher peak platelet (median, 134.0 × 10 9 /L vs . 74.0 × 10 9 /L; P = 0.015 ) and absolute increase (median, 101.0 × 10 9 /L vs . 41.0 × 10 9 /L; P = 0.020 ) after avatrombopag treatment. The responder rate was higher in patients without CLD (100% vs . 76.4%; P = 0.010 ). Combined avatrombopag with other thrombopoietic agents significantly increased platelet count; repeated use of avatrombopag produced similar effects with that of initial treatment. Concerning anticancer treatment effect, patients who responded to avatrombopag had a higher disease control rate. No thrombosis or hemorrhagic events were observed, even in patients with portal vein tumor thrombosis. Conclusion . Avatrombopag was safe and effective and ensured successful implementation of anticancer treatment in liver cancer patients with severe thrombocytopenia, accompanied with or without CLD.